The Necessity of CT Hip Scans in the Investigation of Occult Hip Fractures and Their Effect on Patient Management - Thomas Gatt; Daniel Cutajar; Lara Borg; Ryan Giordmaina (Advances in Orthopedics)
The diagnostic challenge of negative plain radiography in the context of a previously ambulatory patient is increasing with the rise in geriatric trauma. These patients are often diagnosed with small undisplaced fractures of the pelvis and femur which may not alter management. This study aims to assess the frequency at which computed tomography (CT) hip scans altered patient management and whether two X-ray projections of the hip affected fracture detection rate. All CT hip scans performed over a three-year period were identified retrospectively. Only CT hips pertaining to the identification of occult fractures were included in the study. A total of 447 (63.6%) CT hips were performed to exclude an occult fracture, which was only detected in 108 (24.1%) of the scans requested. The majority were subcapital (n = 58, 53.7%) or intertrochanteric (n = 39, 36.1%). There was no significant difference between fracture detection rates when comparing one and two views of the pelvis. 82.4% (n = 89) of occult hip fractures were managed operatively. CT imaging led to a change in patient management in 20% of cases. The frequency at which CT scan detects and alters management in occult hip fractures confirms the justification for its use. Increasing the number of X-ray projection views does not decrease the reliance on CT. Pelvic ring fractures are common in nonambulatory patients following trauma, and if confirmed on initial imaging, subsequent imaging to exclude a concurrent occult hip is unnecessary. The focus of further research should be towards the development of investigation algorithms which decrease the reliance on CT and defining the optimal surgical criteria for occult hip fractures.